The Influence Of Academic Supervision, Instructional Leadership Style, and Work Discipline on Elementary School Quality - Sari, Devi Ranita; Ysh, AY Soegeng; Kusumaningsih, Widya (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
School quality plays a crucial role in supporting student success and ensuring effective educational outcomes. This study aims to analyze the effect of Academic Supervision, Instructional Leadership Style, and Work Discipline on the Quality of Elementary Schools in Dempet District, Demak Regency. Given the increasing demand for school improvement, understanding the contribution of these factors is essential for policymakers and educators. This study employs a quantitative correlational approach with a survey research design. The research population consists of 458 teachers, with a sample of 151 teachers selected through proportional random sampling. Data were collected using a questionnaire and analyzed through descriptive statistics, prerequisite tests, simple linear regression, and multiple regression analysis. The findings indicate that Academic Supervision, Instructional Leadership Style, and Work Discipline significantly contribute to school quality. The regression equation for Academic Supervision is Y = 4.737 + 0.223X1, with an R-Square value of 0.027, indicating a small contribution. Instructional Leadership Style has a greater effect, with the equation Y = 36.022 + 0.967X2 and an R-Square value of 0.238, explaining 23.8% of school quality variance. Work Discipline also plays a significant role, with the equation Y = 48.063 + 0.530X3 and an R-Square value of 0.230. The combined regression model (Y = 4.737 + 0.223X1 + 0.740X2 + 0.406X3) shows an R-Square value of 0.361, indicating that these three factors collectively explain 36.1% of school quality improvement. These findings highlight the importance of strengthening academic supervision, leadership, and teacher discipline to enhance elementary school quality effectively.